COLLABORATIVE GOVERNANCE IN OPTIMIZING WAQF LAND REGISTRATION IN GORONTALO REGENCY - Trezy Andhika; Arifin Tahir; Rusli Isa (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Waqf land registration is essential to the governance of socio-religious assets and requires effective cross-sector collaboration. In Gorontalo Regency, a significant gap between recorded and certified waqf lands indicates structural weaknesses in the governance framework. This study evaluates the design of waqf land registration governance using a collaborative governance perspective and proposes an integrative institutional reconstruction to improve certification outcomes. A qualitative policy case study approach was employed, drawing on waqf and land regulations, technical policy documents, and regional administrative data. The analysis was guided by key dimensions of collaborative governance: starting conditions, institutional design, facilitative leadership, and collaborative processes. The findings show that although formal authority is clearly defined, governance remains fragmented and largely procedural. The absence of a permanent coordination forum, uneven actor capacities, limited information integration, and weak facilitative leadership constrain the development of sustained collaboration. To address these issues, the study recommends institutionalizing deliberative coordination mechanisms, strengthening participatory capacities, integrating information systems, and embedding collective accountability. The research extends the application of collaborative governance to regionally implemented, religion-based public policies.